A study of vocational maturity of senior high school boys and girls in the University of Nueva Caceres during the school year 1975-1976 - Malanyaon, Benigno Ve (Animo Repository, 1976)
This study investigates the difference between career maturity of some senior high school boys with the girls of the University of Nueva Caceres. It also examines the relationship between socio-economic status and the students' vocational development and maturity. The subjects of the study were the graduating high school seniors of school year 1975-1976, selected by random sampling procedure. Two hundred thirteen subjects which constitutes 40% of the total senior high school student population were drawn from eleven sections in the University of Nueva Caseres. The research instruments used in this study were the: 1) Career Maturity Inventory and the 2) Socio-Economic Status Questionnaire. Statistical tools included means and standard deviations of the different variables, frequency and percentage distribution, Pearson Product-Moment Correlation (r), and Fisher's t and Z-test. On the bases of the findings obtained, the writers offers the following conclusions: 1. That no significant difference in the performance of the senior high school boys and girls in career attitude maturity exists. 2. Boys and girls did not differ significantly in the performance in the areas of the career choice competencies namely: Self-Appraisal, Occupational Information, Goal Selection, Planning except in the area of Problem-Solving. 3. Low incidence in vocational maturity exists in both groups. 4. That no significant difference in the proportion of boys and girls who were considered vocationally mature as measured by the CMI. 5. Vocational Maturity as measured by the Career Maturity Inventory (CMI) has no significant relationship to socio-economic status. 6. Implications were suggested focusing on the following: a. value of vocational guidance in the school, b. value of vocational guidance in the homeroom, and c. value of vocational guidance in the home.